2007
DOI: 10.1016/j.radmeas.2007.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Photo-stimulated luminescence and photo-induced infrared absorption in ZnWO4

Abstract: Reflection, luminescence-excitation, luminescence decay kinetics, photo-stimulated luminescence, and photo-induced infrared absorption have been measured for ZnWO 4 crystals in the temperature range of 6−300 K. The results are compared with the previous data. The optical properties of ZnWO 4 are discussed on the basis of the present results, as well as the result of the relativistic molecular orbital calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 10 publications
6
24
0
Order By: Relevance
“…This dependence is typical of the low-energy tails of directabsorption edges with excitonic effects and has been attributed to the dissociation of excitons in the electric fields of polar phonons or impurities. The presence of the Urbach's tail is in agreement with the conclusion drawn from low-temperature measurements performed by Itoh et al [12]. These authors as well as others also concluded that the lowest band-gap of metal tungstates is direct [12,14,19].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This dependence is typical of the low-energy tails of directabsorption edges with excitonic effects and has been attributed to the dissociation of excitons in the electric fields of polar phonons or impurities. The presence of the Urbach's tail is in agreement with the conclusion drawn from low-temperature measurements performed by Itoh et al [12]. These authors as well as others also concluded that the lowest band-gap of metal tungstates is direct [12,14,19].…”
Section: Resultssupporting
confidence: 90%
“…Regarding, the steep absorption edge, as stated in the literature [12,14,21,28], we found that it exhibits an exponential dependence on the photon energy following the Urbach's law [29]. This dependence is typical of the low-energy tails of directabsorption edges with excitonic effects and has been attributed to the dissociation of excitons in the electric fields of polar phonons or impurities.…”
Section: Resultssupporting
confidence: 74%
“…The red shift of the band allows to exclude the presence of the quantum size effect, which should cause, on the contrary, a blue shift. The luminescence decay kinetics in nanoparticles is faster than in microcrystalline ZnWO 4 [21] and cannot be described by three component exponential decay, associated with the three types of self-trapped excitons [34], opposite to the case of microcrystalline [21,26] or single-crystal [35] ZnWO 4 . The shift of the luminescence band position to lower energies and the acceleration of the luminescence kinetics can be explained by a significant deformation of WO 6 octahedra and by an influence of surface defects in nanoparticles.…”
Section: Resultsmentioning
confidence: 89%
“…In pure ZnWO 4 the origin of the main band at 2.5 eV has been previously assigned to radiative electron transitions within the [WO 6 ] 6− anions [11,12]. At the same time, the band at ∼ 2 3 eV has been attributed to recombination of e-h pairs localized at oxygen-atom-deficient tungstate ions [15,16] or distorted WO 6 octahedra [17]. The origin of the last band at 3.0 eV appearing in the solid solutions is attributed to the interference between the broad luminescence band of the WO 6 groups and the absorption band of the NiO 6 groups.…”
Section: Resultsmentioning
confidence: 95%
“…In particular, the intrinsic luminescence band, observed at room temperature at about 2.5 eV, has been attributed to a charge transfer between oxygen and tungsten ions in the [WO 6 ] 6− anions [11][12][13][14]. The contributions from defects and distorted tungsten-oxygen octahedra have been also observed [15][16][17]. Up to now, most fundamental studies on tungstates have been performed on single-crystal samples.…”
Section: Introductionmentioning
confidence: 99%